2022
DOI: 10.3390/agronomy12020240
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Year Study on Yield and Yield Components of Maize-White Bean Intercropping Systems under Different Sowing Techniques

Abstract: Food security is directly coupled with enhanced production under optimized cropping intensity. Intercropping is a diversified and sustainable agricultural technique with optimized cropping intensity. Intercropping is used to obtain a higher yield and more balanced products per unit area. This study was performed at Aidyn Research Institute, Nur Sultan, Kazakhstan, in 2018 and 2019 to identify the effects of different sowing patterns on maize–white bean (Zea mays–Phaseolus vulgaris) sowing systems. The field ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…The effect of raising the N rate on maize production was stronger in early spring sowing than in late spring sowing, owing to the improved effect of N-fertilizer on kernels per ear (Coelho et al, 2022). The suitable N fertilizer rate and time enhances grain weight as a result of increasing effective grain-filling duration and rate (Abdelsalam et al, 2019;Wei et al, 2019;Hammad et al, 2022;Zhanbota et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The effect of raising the N rate on maize production was stronger in early spring sowing than in late spring sowing, owing to the improved effect of N-fertilizer on kernels per ear (Coelho et al, 2022). The suitable N fertilizer rate and time enhances grain weight as a result of increasing effective grain-filling duration and rate (Abdelsalam et al, 2019;Wei et al, 2019;Hammad et al, 2022;Zhanbota et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…These findings are related to those of Rinehardt et al (2004) and Rafi et al (2015) , they indicated that plant height was found to be significantly influenced by plant space, as plants luxuriously utilized all resources and light interception was also better. Plant space affects light interception, moisture availability, nutrient uptake, humidity, and weed infestation ( Stephenson, IV et al, 2011 ; Zhanbota et al, 2022 ) and thus influence plant height, fruiting behavior, maturity, and final yield. More competition among plants suppresses plant growth under narrow spacing.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, the efficiency of such mixtures depends largely on the growth habit and diversity of the crops, the planting density, the time of planting of the individual crops, the location, and the weather conditions during the growing seasons [ 103 , 114 , 115 ]. We have shown that intercropping offers numerous advantages and appears to be an important strategy for the future.…”
Section: Exploiting Heterogeneity and Intercropping Systems In Breedi...mentioning
confidence: 99%